User-Centric UI/UX Design in HR Applications: Boosting Employee Learning and Retention - Pringgabayu, Dematria; Ramadhian, Mochamad Arief Rahman; Muzakky, Faqih Ahmad; Sugiana, Neng Susi Susilawati (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
This study examined the impact of user-centric UI/UX design in HR applications on employee learning and retention. With the growing use of digital platforms for employee training and development, the effectiveness of these tools depended significantly on an intuitive and engaging design. This research identified key design principles, such as simplicity, accessibility, and personalization, which enhanced user engagement within HR applications. Findings indicated that interactive features like progress tracking and real-time feedback created a more satisfying learning experience. The results demonstrated that user-centered UI/UX design improved training retention, as employees were more likely to engage with and retain information presented in a visually appealing and accessible format.